Comparative study of Silver Sulfadiazine with other materials for healing and infection prevention in burns: A systematic review and meta-analysis - Nímia, Heloisa Helena; Carvalho, Viviane Fernandes; Isaac, Cesar; Souza, Francisley Ávila [UNESP]; Gemperli, Rolf; Paggiaro, André Oliveira (Elsevier, 2018)
The aim of this systematic review with meta-analysis was to compare the effect of Silver Sulfadiazine (SSD) with other new dressings, with or without silver, on healing and infection prevention in burns. The electronic search was carried out in the electronic databases of Pubmed, ScienceDirect, Lilacs and BVS. The articles included were randomized clinical trials about burn treatment with SSD, which evaluated the healing and infection of burn wounds in humans. The exclusion criteria included articles, editorials and letters published in the form of abstracts, unpublished reports and case series, cross-sectional, observational experimental studies, and the use of sulfadiazine for other types of wounds. The search identified 873 references, and 24 studies were included in accordance with the eligibility criteria. The results showed a statistically favorable difference related to the time of healing for silver dressings (p < 0.0001; MD 3.83; 95% CI 2.03–5.62) and dressings without silver (p < 0.007; MD 2.9; 95% CI 0.81–5.00) in comparison with SSD. The rate of infection showed no difference in the group treated with SSD compared with the group treated with dressings containing silver (p > 0.05). The rate of infection was significantly higher in the SSD group compared with the group treated with dressings without silver (p < 0.005; MD 25.29% and MD 12.97%). Considering the clinical trials conducted up to the present time, the authors concluded that new dressings with and without silver show better results than SSD for wound healing, and burns treated with dressings without silver are less likely to become infected than burns with SSD. No differences between SSD and new silver materials were observed in relation to infection prevention.
Keywords: Burns; Infection; Occlusive dressings; Silver Sulfadiazine; Wound healing